Impacts of scheduled desludging on quality of water and wastewater in Wai city, India. (October 2022) - Jaiswal, Jigisha; Mehta, Dinesh; Mehta, Meera
The common practice for desludging of septic tanks is 'demand-based desludging' rather than a regular service. Such practices have adverse social and environmental impacts. Scheduled desludging is advocated to maintain the performance of septic tanks and avoid adverse effects on the environment. Wai, a small town in the state of Maharashtra, India, is the first city in India to implement scheduled desludging. This paper discusses impact of scheduled desludging on water quality. The quality of water before scheduled desludging and after scheduled desludging is assessed. It describes monitoring the quality of groundwater, river water, effluent from drains and supernatants from septic tanks. It reflects the linkages of scheduled desludging and improved supernatants and drain water quality which as a result improves the river and groundwater quality. The results suggest positive impact of regular desludging on the performance of septic tanks. This has led to improvement in the quality of drain water, ground water and river water.